2011
DOI: 10.1021/ja204366b
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Dendronized Perylene Bisimides into Complex Helical Columns

Abstract: The synthesis of perylene 3,4:9,10-tetracarboxylic acid bisimides (PBIs) dendronized with first-generation dendrons containing 0 to 4 methylenic units (m) between the imide group and the dendron, (3,4,5)12G1-m-PBI, is reported. Structural analysis of their self-organized arrays by DSC, X-ray diffraction, molecular modeling, and solid-state (1)H NMR was carried out on oriented samples with heating and cooling rates of 20 to 0.2 °C/min. At high temperature, (3,4,5)12G1-m-PBI self-assemble into 2D-hexagonal colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
130
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 86 publications
4
130
0
1
Order By: Relevance
“…5,6 Practical applications of these systems are hampered by many issues, including poor solubility, high melting temperatures, air sensitivity, difficult processability, low charge carrier mobilities and short charge carrier lifetimes. 1,[6][7][8] Furthermore, the kinetically controlled polymorphism of large PBI assemblies hinders their structural analysis, [9][10][11] especially by commonly-used single crystal X-ray diffraction analysis. Functionalization of the bay positions of PBI with halogens including fluorine, chlorine and bromine has been proven to address some of the limitations of non-halogenated PBI building blocks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Practical applications of these systems are hampered by many issues, including poor solubility, high melting temperatures, air sensitivity, difficult processability, low charge carrier mobilities and short charge carrier lifetimes. 1,[6][7][8] Furthermore, the kinetically controlled polymorphism of large PBI assemblies hinders their structural analysis, [9][10][11] especially by commonly-used single crystal X-ray diffraction analysis. Functionalization of the bay positions of PBI with halogens including fluorine, chlorine and bromine has been proven to address some of the limitations of non-halogenated PBI building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The PBI derivatives self-organized to form a range of 2D and 3D phases, of which the least encountered 3D thermodynamic products are the most desirable for technological applications. 11 Here we report the synthesis and structural analysis of five Cl 4 PBI derivatives with n and m chosen to promote thermodynamically controlled formation of 3D crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was shown that supramolecular interactions of a chiral electron-acceptor molecule with a columnar supramolecular dendrimer selects the twist sense of the helical column [52], while the covalent attachment of a chiral alkyl chain at the periphery of a C 3 -symmetric dendrimer mediates transfer, amplification, and thermal inversion of chirality in the corresponding supramolecular assembly [85]. Similarly, a homochiral unit could potentially be introduced in other electronic materials composed of donor/acceptor self-assembled dendrimers [30,86,87] in order to tune their structural and electronic properties. This strategy could also be used to monitor the structure and function of self-organizable dendronized polymers.…”
Section: Discussionmentioning
confidence: 99%
“…While Perylene has been utilized in the synthesis of multiple charge transfer salts, it has also been integrated into organometallic complexes having ruthenium, palladium and silver metal centers and as essential components within Perylene 3,4:9,10-tetracarboxylic acid bisimides (PBIs), the latter being building blocks having applications as pigments, protein tags, and within organic field effect transistors (OFETs) and organic solar cells due to their robust photochemical, thermal stability and high fluorescence quantum yields [13][14][15][16][17][18][19][20][21][22]. In addition to these, Perylene has also been co-crystallized with various organic acceptors, among them TCNQ (TCNQ = 7,7,8,8-tetracyanoquinodimethane) with which it forms both 1:1 and 3:1 phases and fluoranil (fluoranil = 2,3,5,6-tetrafluoro-1,4-benzoquinone), complexes known to be photoconductors [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%